História de Formação de Alfabetizadoras: A disciplina Didática da Linguagem no Magistério 1971 a 1985 - Macedo, Tatiane Batista (2009)
In the literacy teachers training history field of discussions, this research discusses questions like literacy teachers training in a Teacher-training College, schedule and school disciplines, and contents and teaching methodologies. It is about a qualitative research that used of documental and oral crossed information, by a documental search and Oral Theme History. The objective of this study was to analyze literacy teachers training on the Teacher-training College by the Language Didactic discipline on a period between 1971 and 1985, also researching the teaching methodology contents studied on this discipline and the methodologies used by the training teachers in their classes. To reach this objective, was analyzed the Teacher-training course and the course disciplines legislation, class-books and the testimony of the teachers that ministered the Language Didactic discipline classes. The research results shown that the most studied contents were the literacy training methods and their techniques and methodology application. The teachers trainers reveled that their pedagogic practices had the methodological teaching practices as a priority instead the learning theories and in their classes they used lots of technical proceedings like teaching methodologies. At this period they had the concept that the Teacher-training College students should learn how to give classes recipes .